The Impact of Performance Appraisal on Employee Motivation at PT. Galatta Lestarindo Medan - Bestadrian Prawiro Theng (Universitas Muhammadiyah Palu, 2023)
The effect of performance appraisal process on employee motivation established that the system is important for employee motivation. Performance appraisal system has helped improve job performance at work. But so many company forget about how useful this system is, which lead to decrease of employee motivation, and PT. Galatta Lestarindo Medan also having this problem, such as high of turnover, it happened because the employees are unmotivated and unsatisfied to continue working in this company. The population that is used in the research is the total employees who are active working September 2015 in PT. Galatta Lestarindo Medan that are 37 people. The sampling technique is called as census sampling. Census sampling method is method which takes all the population as the sample. In analyzing questionnaires, the writer used validity test and reliability test, to analyze the data, use statistics, correlation test, determination test, linear regression, and hypothesis test. The correlation test shows that performance appraisal really have an impact through employees performance at PT. Galatta Lestarindo Medan, the result is positive and strong effect on employees’ performance at PT. Galatta Lestarindo Medan. zcount > ztable (5.16> 1.96), This means the Null hypothesis (Ho) is rejected and the alternative (Ha) is accepted.